A Horizon Scan of Emerging Global Biological Conservation Issues for 2020. (January 2020) - Sutherland, William J.; Dias, Maria P.; Dicks, Lynn V.; Doran, Helen; Entwistle, Abigail C.; Fleishman, Erica; Gibbons, David W.; Hails, Rosie; Hughes, Alice C.; Hughes, Jonathan; Kelman, Ruth; Le Roux, Xavier; et al.
Abstract : In this horizon scan, we highlight 15 emerging issues of potential relevance to global conservation in 2020. Seven relate to potentially extensive changes in vegetation or ecological systems. These changes are either relatively new, for example, conversion of kelp forests to simpler macroalgal systems, or may occur in the future, for example, as a result of the derivation of nanocelluose from wood or the rapid expansion of small hydropower schemes. Other topics highlight potential changes in national legislation that may have global effect on international agreements. Our panel of 23 scientists and practitioners selected these issues using a modified version of the Delphi technique from a long-list of 89 potential topics. Highlights: We present 15 issues that emerged from our 11th annual horizon scan of global biological conservation. Issues were identified by a diverse group of scientists and practitioners. The group scored the long-list of 89 issues using a Delphi-like process. Issues were ranked according to novelty, relevance, and potential impact on biological conservation. The top-38 ranked issues were debated at a workshop in Cambridge, UK, with each topic scored immediately following the discussion. Emerging themes include changes in national legislation that could affect international agreements; recognising ecocide as an international crime; and the global decline in kelp forests. Other issues include the increasing use of traditional Asian medicine; the spread of the Asian long-horned tick; use of artificial wombs in mammalian conservation; and the impact that the shrinking ozone hole may have on Antarctic sea ice.